Numerical Simulation Research on Hydraulic Fracturing Promoting Coalbed Methane Extraction - Fan Yongpeng; Shu Longyong; Huo Zhonggang; Hao Jinwei; Yang Li (Shock and Vibration)
Although hydraulic fracturing technology has been comprehensively investigated, few scholars have studied the influence of hydraulic fracturing on the effect of coalbed methane (CBM) extraction, and few considered the interaction between water and CBM in the research process, which is not conducive to guiding the engineering design of hydraulic fracturing wells. In this work, a hydraulic-mechanical-thermal coupled model for CBM extraction in hydraulic fracturing well is established; it combines gas-liquid two-phase infiltration, where nonisothermal adsorption is also considered. The COMSOL Multiphysics software is used to carry out the numerical simulation study of the CBM extraction process in hydraulic fracturing well and analyze the influence of coalbed permeability, initial methane pressure, and fracture length on CBM extraction in hydraulic fracturing well, and the results show that the hydraulic-mechanical-thermal coupled model for CBM extraction can be used for CBM extraction research in hydraulic fracturing well. The initial coalbed permeability, initial gas pressure, and fracture length all affect the migration speed of CBM to surface well in different ways and have a greater impact on the CBM production rate of hydraulic fracturing well. The greater the initial coalbed permeability and methane pressure are, the longer the fracture length is and the greater the CMB production rate of hydraulic fracturing well is. The change trend of coalbed permeability during the extraction process of surface fracturing well is directly related to the state of the reservoir. The factors of stress, temperature, and CBM desorption jointly determine the increase or decrease of coal seam permeability.